Introducing of Financial Literacy in Shaping Saving Behavior in Elementary School Students - Hafitah, Sari Yuliani; Sakti, Asri Wibawa (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study is to analyze the extent of understanding of financial literacy in improving saving behavior in elementary school students. The method used in this research is a descriptive quantitative method. The results showed that the average post-test score of students was 71% greater than the average pre-test score of 35%, so the difference was 36%. On the basis of school indicators, financial literacy training has never been carried out and there has been no application of financial literacy values in learning. Therefore, this financial literacy program is implemented in order to improve saving behavior and can even be taken into consideration for study so that it can provide solutions in managing and making appropriate financial decisions. Starting from the curriculum level which is the basis for teaching, appropriate materials and materials, competent and dedicated teaching staff are needed for smooth implementation of financial literacy education in schools.